Upaya Mempertahankan Kebersihan Jalan Napas Dengan Fisioterapi Dada Pada Anak Pneumonia - Sari, Dewi Purnama, Irdawati, S.Kep.,Ns.,M.Si.,Med (2016)
Pneumonia is an inflammatory process in the alveoli of the lungs caused by microorganisms and non-food or icroorganisms that aspiration of gastric contents, hirokarbon, lipoid material, hipersensititas reactions, drug-induced and radiation. The microorganisms that cause pneumonia are Streptococcus pyogenes, Staphylococcus aureus, Haemophyllus influenzae, Mycobactrium tuberculosis, Salmonella, Scherichiacolli, Pneumocystis jirofeci. Pneumonia is a disease that can be suffered by all ages, both men and women. Central Java Province precisely in Boyolali case of pneumonia had the same number of patients for the last few years. One of the problems due to neumonia are the accumulation of sputum in the respiratory tract. Some clinical symptoms as a result of the accumulation of sputum are nostril breathing, increased respiratory rate, dypsneu, krekels sound occur when auscultated, and difficulty breathing. Breathing ifficulties will hamper the fulfillment of the supply of oxygen so the oxygen supply is reduced. The reduced supply of oxygen in the body to make cell death, hypoxemia and decreased consciousness. Pneumonia treatment in patients with airway hygiene issues aimed at cleansing the respiratory tract that supply oxygen into the body can be met and disruption due to reduced oxygen supply does not occur. Methods applied in dealing with these airway disorders cleanliness in accordance with the nursing care of patients with respiratory disorders, one of the independent nursing actions taken to clean up the respiratory tract of sputum that chest physiotherapy. After doing chest physiotherapy in patients, sputum successfully removed from the action it can be concluded that the cleanliness of the patient's airway disorders resolved. Interventions followed by encouraging the patient's mother to give chest physiotherapy in children independently if the child recurred at home.